Mechanism of deep cracks in the left bank slope of Jinping first stage hydropower station - Qi, Shengwen; Wu, Faquan; Yan, Fuzhang; Lan, Hengxing (Engineering geology, 2004)
The proposed Jinping first stage hydropower station is located on the middle reach of the Yalongjiang River, Sichuan Province, PR China. It consists of a double-curvature arch dam with a maximum height of 305 m, which will be the highest in the world. Cracks are well developed in the left bank slope of the Pusiluogou, the dam site of Jinping first stage hydropower station. Some cracks are even developed at the horizontal distance into rock face (in this paper, the term “horizontal depth” was used to describe the horizontal distance into face of the slope) beyond 200 m, and these cracks are here referred to as deep cracks. The distribution of these deep cracks is far beyond people's experiences in common unloading zones, so the mechanism of the deep cracks is put forward as a new subject. Since these cracks are significant for the stability of the slope, their mechanism becomes one of the key engineering geology problems. A comprehensive study is made in this paper on the distribution characteristics of the cracks as well as their deformation features. The factors that influence their distribution and deformation feature are also analyzed by means of geology, mechanics and numerical simulation. An important conclusion is consequently reached that deep cracks occurred as a result of release of high ground stress including gravitational stress and tectonic stress. The formation of the deep cracks in the slope is a result of unloading process under favorable geology conditions. Fast crust uplift and quick river cutting and high tectonic stress are indispensable regional geological condition, steep and high geometry condition provides favorable geometry condition, hard at the lower part and soft at the upper part of the slope offers suitable rock combination condition, and back facing bending planes and consequent discontinuities supply suitable structure of the slope.